Exploring the Therapeutic Effects of Transcranial Direct Current Stimulation on Sleep Quality Among Patients Under Methadone Maintenance Treatment - Sadeghi Bimorgh, Mohammad; Omidi, Abdollah; Ghoreishi, Fatemeh Sadat; Rezaei Ardani, Amir; Ghaderi, Amir; Banafshe, Hamid Reza (International Journal of Medical Toxicology and Forensic Medicine, 2020)
Background: Patients under Methadone Maintenance Therapy (MMT) are susceptible to several problems, including sleep disturbances and risk of relapse. The present study aimed to assess the effect of transcranial direct current stimulation (tDCS) on sleep quality of addicts under MMT. Methods: This clinical trial was conducted on 27 male patients who underwent maintenance methadone therapy in MMT clinics of Mashhad City, Iran. They were divided into the experimental and sham groups. The experimental group received seven 20-min sessions of tDCS every other day. In the sham group, the electrical current was delivered for a few seconds, but the electrodes were remained to the end of the session. Sleep quality was measured at baseline, during, and after the intervention by Pittsburg Sleep Quality Index (PSQI). The obtained data were analyzed by descriptive statistics such as mean and standard deviation and inferential statistics, such as t test, Chi-square, Mann Whitney, and Fischer exact test in SPSS v. 25. Results: The difference between the two groups after tDCS in sleep duration was significant (P=0.04). In the experimental group, the total score of sleep had a reducing trend (P<0.000), while in the sham group, the overall score in 3 phases of evaluation had no significant change (P=0.19). However, the rate of inappropriate sleep quality was not significant between the two groups after the intervention (P=0.12). Conclusion: This trial demonstrated the positive effect of tDCS on sleep quality in patients under MMT programs. Further studies are needed to confirm our findings.